2011
DOI: 10.1021/jp204175e
|View full text |Cite
|
Sign up to set email alerts
|

Surface Termination Control in Chemically Deposited PbS Films: Nucleation and Growth on GaAs(111)A and GaAs(111)B

Abstract: This study addresses the question of whether chemically deposited PbS thin films grown on GaAs(111) are affected by the oppositely terminated substrate surfaces, gallium terminated GaAs(111)A and arsenic terminated GaAs(111)B. The differences in PbS film deposition pathway in both cases of substrate surface termination were investigated using X-ray photoelectron spectroscopy (XPS), Raman scattering, and contact potential difference (CPD) measurements. The morphology, microstructure, and crystallographic orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 49 publications
1
16
0
Order By: Relevance
“…Both the peak transitions of Pb(4f 7/2 ) centered at 137.4 eV and S(2p) centered at 160.6 eV indicated the unoxidized nature of the deposited lead sulfide clusters. [26] A further quantitative analysis of XPS results revealed that the ratio of Pb to S was found to be about 1:1, which doubly confirmed the deposition of PbS clusters. Given the presence of size-defined (PbS) 32 clusters on the surface as the starting point, we were assured that the observed STM images were the result of two-dimensional nucleation between (PbS) 32 clusters and/or between nano-blocks composed of multiple (PbS) 32 units.…”
Section: Lead Sulfide: Its Clusters and Its Embryonic Crystalmentioning
confidence: 72%
“…Both the peak transitions of Pb(4f 7/2 ) centered at 137.4 eV and S(2p) centered at 160.6 eV indicated the unoxidized nature of the deposited lead sulfide clusters. [26] A further quantitative analysis of XPS results revealed that the ratio of Pb to S was found to be about 1:1, which doubly confirmed the deposition of PbS clusters. Given the presence of size-defined (PbS) 32 clusters on the surface as the starting point, we were assured that the observed STM images were the result of two-dimensional nucleation between (PbS) 32 clusters and/or between nano-blocks composed of multiple (PbS) 32 units.…”
Section: Lead Sulfide: Its Clusters and Its Embryonic Crystalmentioning
confidence: 72%
“…17 The absence of any spectral intensity in the S(2p) region above 164 eV indicates that there is no sulfur oxidation. This data is shown in Figure 6.…”
Section: Experimental Methods and Results: Supporting Evidencementioning
confidence: 99%
“…12 It is reasonable to assume that during nucleation, transformations with smallest atomic displacements and lattice strains are normally favored with respect transformations which involve greater changes. Furthermore, comparison of the radii of Ga in GaAs and Pb in PbS, point out very close proximity (ca.…”
Section: ■ Results and Discussionmentioning
confidence: 99%